Significance of the timing of ureteral ligation on prognosis during radical nephroureterectomy for upper urinary tract urothelial cancer. (29th November 2020) - Inokuchi, Junichi; Kuroiwa, Kentaro; Nishiyama, Hiroyuki; Kojima, Takahiro; Kakehi, Yoshiyuki; Sugimoto, Mikio; Takenaka, Atsushi; Fujimoto, Kiyohide; Yamaguchi, Raizo; Habuchi, Tomonori; Hashine, Katsuyoshi; Mizusawa, Junki; et al.
Abstract : Objectives: To investigate the impact on intravesical recurrence and prognosis according to the ureteral ligation timing during radical nephroureterectomy for upper urinary tract urothelial carcinoma. Methods: We carried out a retrospective chart review of 664 patients with non‐metastatic upper urinary tract urothelial carcinoma who underwent radical nephroureterectomy with ureteral ligation (supplementary analysis of JCOG1110A). We excluded patients with previous and/or synchronous bladder cancer, clinically node‐positive disease, no ureteral ligation data, those without ureteral ligation and those with any missing data. We investigated the cumulative incidence of intravesical recurrence and cancer‐specific mortality, and overall survival between patients with ureteral ligation before renovascular ligation (early ureteral ligation), or ureteral ligation after renovascular ligation (late ureteral ligation). Results: Early and late ureteral ligation was carried out in 243 patients (36.6%) and 421 patients (63.4%), respectively. Intravesical recurrence occurred in 218 patients (32.8%) during follow up (median 3.9 years). No significant difference in the intravesical recurrence was found between early and late ureteral ligation groups. Meanwhile, survival in the early ureteral ligation group was significantly worse compared with the late ureteral ligation group. Multivariable analysis showed that early ureteral ligation was an independent prognostic factor for overall survival (hazard ratio 1.88, 95% confidence interval 1.24–2.85, P  = 0.003) and cancer‐specific mortality (hazard ratio 1.93, 95% confidence interval 1.14–3.25, P  = 0.014). Conclusions: Our findings suggest that the incidence of intravesical recurrence is not affected by the timing of ureteral ligation during radical nephroureterectomy. However, early ureteral ligation might have a negative impact on survival outcomes.